TELAAH PERAN LURAH DAN CAMAT DALAM PROGRAM PERCEPATAN PEMBANGUNAN KELURAHAN BERMARTABAT (P2KB) DI KOTA BANDUNG - Gedeona, Hendrikus Triwibawanto (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2011)
Roles of government and bureaucracy in development program in developing countries are still dominant. The government and its bureaucracy still become the main actors, although there has been a shift in public administration paradigm from government approach to governance approach. The situation also appears in the context of local development. The role of local government, including Bandung City municipality, is still dominant in implementing local development programs. Bandung City Local Government along with its 'Lurahs' and 'Camats' implemented in village (kelurahan) Development Acceleration Program (P2KB) in 2010 in order to improve citizens welfare. The program aimed at empowering citizens through participatory and community based development approach. Its interesting to know how Lurahs and Camats played their roles in the development acceleration program so that the program could run optimally.